Chitin whiskers enhanced methacrylated hydroxybutyl chitosan hydrogels as anti-deformation scaffold for 3D cell culture. (15th March 2023) - Zhu, Yue; Qin, Di; Liu, Jinfeng; Wu, Guangsheng; Wang, Haonan; Wu, Feifei; Liu, Yixuan; Liu, Ya; Cheng, Xiaojie; Chen, Xiguang
Abstract: Hydrogel, as three-dimensional (3D) cell culture scaffold, is an effective strategy for tissue and organ regeneration due to their good biocompatibility, biodegradability and resemblance to body microenvironments in vivo. However, the inherent weak mechanical properties and strong shrinkage of hydrogels during cell culture hinder its application in clinical. In this study, a two-component thermo/photo dual-sensitive hydrogel (M/C) was prepared from methacrylated hydroxybutyl chitosan (MHBC) and chitin whisker (CHW) via physical and chemical cross-linking methods. M/C hydrogel showed a special internal structure with lamellar arrangement. The rheological properties of the hydrogels could be regulated with the change of M/C ratio. It is worth emphasizing that the mechanical properties, shrinkage resistance and cellular capacitances of the M/C hydrogel were improved with the addition of CHW. Moreover, the M/C hydrogel not only exhibited excellent degradability and antibacterial properties, but also significantly promoted the adhesion and proliferation of MC3T3-E1 cells in vitro. Therefore, the M/C hydrogel showed a wide application potential in tissue regeneration as a 3D cell culture scaffold. Graphical abstract: Unlabelled Image